2020
DOI: 10.1101/2020.08.25.267658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global and Local Mutations in Bangladeshi SARS-CoV-2 Genomes

Abstract: Corona Virus Disease-2019 (COVID-19) warrants comprehensive investigations of publicly available Severe Acute Respiratory Syndrome-CoronaVirus-2 (SARS-CoV-2) genomes to gain new insight about their epidemiology, mutations and pathogenesis. Nearly 0.4 million mutations were identified so far in ∼60,000 SARS-CoV-2 genomic sequences. In this study, we compared 207 of SARS-CoV-2 genomes reported from different parts of Bangladesh and their comparison with 467 globally reported sequences to understand the origin of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…On the other hand, 12 sequences that did not belong to any clusters were found to be similar with sequences from Europe, including United Kingdom, Germany, France, Italy, and Russia, while one of these sequences was close to the sequence reported from the USA ( Shishir et al, 2021 ; Hasan et al, 2020 ). The underlying link of Bangladeshi SARS-CoV-2 isolates with part of a haplotype observed high in Europe ( Shishir et al, 2021 ; Mahmud et al, 2020 ).…”
Section: Introductionmentioning
confidence: 69%
“…On the other hand, 12 sequences that did not belong to any clusters were found to be similar with sequences from Europe, including United Kingdom, Germany, France, Italy, and Russia, while one of these sequences was close to the sequence reported from the USA ( Shishir et al, 2021 ; Hasan et al, 2020 ). The underlying link of Bangladeshi SARS-CoV-2 isolates with part of a haplotype observed high in Europe ( Shishir et al, 2021 ; Mahmud et al, 2020 ).…”
Section: Introductionmentioning
confidence: 69%
“…It is reported that D to G mutation at position 614 (D614G) in the spike glycoprotein which is originated from Europe or China is a signi cant variation in changes of the secondary structure of protein [39] [8]. D614G mutation started in all affected regions such as Bangladesh (with 95.6% D614G mutation), Italy, Spain, North America and European countries [40] [41]. , amino-acid substitution 1109 (F→L) and 76th (S_T76I) position at spike protein found in Bangladeshi and Indonesian strain respectively [37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 87 unique amino acid changes were revealed and were categorized as originating from different cities of Bangladesh. The analyses would increase our understanding of variations in virus genomes circulating in Bangladesh and elsewhere and help develop novel therapeutic targets against SARS-CoV-2 [16]. This correlation indicates that the genomes containing D 614G mutation are more prone to bear other mutations which may facilitate the notion that the link of this mutation with the transmission and pathogenesis of SARS-CoV-2 [14].…”
Section: Bangladesh Scenariomentioning
confidence: 92%